A novel approach towards investigating the performance of different PVT configurations integrated on test cells: An experimental study. (July 2019) - Tomar, Vivek; Norton, Brian; Tiwari, G.N.
Abstract: This study elaborates the theoretical and experimental analysis for the effectiveness of different photovoltaic thermal (PVT) configurations along with their building implications. An experiment was performed on especially designed four identical prototype test cells emphasise the building integration photovoltaic thermal (BiPVT) systems. A comparative analysis of four different possible PVT configurations integrated on identical test cells namely; Case 1: Glass-to-glass PV with duct integrated on a test cell, Case 2: Glass-to -glass PV without duct integrated on a test cell, Case 3: Glass to tedlar PV with duct integrated on a test cell and Case 4: Glass to tedlar PV without duct integrated on a test cell was carried out. Analytical model of the electrical and thermal performance for different cases was developed and experimentally validated in outdoor conditions. On the basis of the correlation coefficient (r) and root mean square percent deviation (e), a fair agreement between theoretically calculated and experimentally observed values is achieved. The glass to glass PV module gives better both electrical and thermal performance with hourly average η m 12.65% and 12.70% for case 1 and 2 respectively. Similarly, the hourly average η ith was observed 32.77% and 25.44% for case 1 and 2 respectively. Further, thermal load levelling with varying packing factor, mass flow rate of air through the PV integrated duct, absorptivity (degradation effect) and transmittivity (dusting effect) are also discussed. Highlights: Potential of different photovoltaic-thermal (PVT) configuration for space heating is explored. Thermal model for different PVT configurations integrated on prototype test cells is developed. Test cells based experiments are performed for different PVT configuration in outdoor environment. Thermal load levelling (TLL) with varying packing factor and ducted air mass flow rate is considered. Effect of absorptivity (degradation effect) and transmittivity (dusting effect) on TLL is also carried out.